The influence of waste motor engine oil in warm mix asphalt - Siti Noor Farzana, Ariff (2019)
There are many studies have been done to determine the suitable waste materials that can be used in order to improve resistance to rutting and fatigue cracking due to binder hardening and improve adhesion of binder to aggregate. In this study, the performance of Waste Motor Engine Oil (WMEO) as bitumen modifier in asphalt concrete pavement was investigated. This study focuses on the addition of WMEO at different percentages, namely, 0%, 3%, 4% and 5% by the weight of bitumen. The aim of this study is to investigate the effect of WMEO on engineering properties of Asphaltic Concrete 14. The WMEO was blended together with bitumen using a high shear mixer at a constant speed of 1000rpm for 1 hour at 140˚C before being used for performance tests. The performance of the samples was evaluated through Marshall Stability, Resilient Modulus and Dynamic Creep test.